The Impact of Facebook Upon Social Skills of Young People - a Business Employment Perspective - Irina Maiorescu; Răzvan Dina; Alexandru Doru Pleșea; Alecu Felician (Amfiteatru Economic Journal, 2015)
Social networks can be successfully used to promote any business, being developed in such a way to allow both individuals and business organizations to interact one with another. Companies may obtain important information about users of social networks which will help to a better understanding of their profile and needs and, consequently, to build their marketing and sales strategies. According to the latest data, Facebook is the most popular social network, with the highest number of registered users from all over the world. The current paper aims to determine the way Facebook users – and more precisely young students belonging to Romanian economic field, behave in respect to this social network from the point of view of information valuable for businesses. The findings of the paper are based on a survey deployed in 2014 and they reveal that although the time spent for online social interaction with friends is longer than the time spent for face to face discussions, users' social skills needed for their future employment do not seem affected.
Keywords: L14; L86; M00; 330; social networks; Facebook; profile identity; business